Celebrity And Audience Characteristics on Satisfaction, And Repeat Watch Intention on Korean Tv Drama - Azaze Azizi Abdul Adis; Hyung, Jun Kim; Mohd Rizwan Abdul Majid; Izyanti Awang Razli (Universiti Malaysia Sabah, 2017)
The prevailing trend of Korean Pop culture, Hallyu, has spread rapidly to Asian countries such Malaysia, Japan, China, Indonesia, Thailand, Vietnam and Taiwan. The influenced of such culture has further reached to other countries such as the Middle East, Europe and America. As the result, the Korean dramas, fashions, and music becoming a hot trend and culture in Asian nations. The study examines the relationship between celebrity and audience characteristics on TV drama satisfaction and repeats watch intention. A total of 596 young Malaysian consumers participated in this study. Attractiveness, credibility, commitment, and connectedness were found to effect the satisfaction of watching Korean drama. In addition, consumer satisfaction toward Korean TV drama does influence their repeat watch intention. However, an involvement of audience was not found to affect TV drama satisfaction. Recommendation and suggestion for future research were also discussed to improve audience satisfaction and ultimately increased the repeat watch intention towards Korean TV drama.